Prathyoushadha Prayoga of Upavisha in Kriyakoumadi-A Review Article. - Alex, Littija; Chaitra , H (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: Ayurveda is covered in a number of regionally written books. One such book that is popular in Kerala is Kriya koumadi. It is among the most well-liked and often used books in toxicology. It offers a number of simple, workable formulae that may quickly be created and used to cure toxic diseases. A few essential criteria, including as origin, base, features, and potency, are used to categorize poisons. Upavisha-related symptoms are less toxic, less severe, and often not life-threatening, and their toxicity may be controlled with therapeutic therapies. In addition to providing an in-depth analysis of each of the 11 Upavisha and their treatments, Kriyakoumadi also offers a variety of simple, doable remedies that may be used to reduce toxicity. Material and Methods: Consulted mainly from kriya Koumadi, famous toxicology book in kerala, from a range of databases websites and publications. Aim: By learning about the Prathyoushadha (medicine which is used for pacifying the poison) for the Upavisha (semipoisonous substances) aims to raise public knowledge. Result: Upavisha classification was done and Prathyoushadha for each upavisha has been documented Discussion and conclusion: As our forefathers, the Vishavaidyas, showed, even with less advanced medical technology than we presently have, these remedies may result in amazing outcomes in situations of poisoning. If the Vishavaidyas of today spread more essential knowledge about poison management, the human species would tremendously benefit. Additionally, it will help throw light on the traditional regional practices that are still observed in many parts of the world.